To determine whether the function \( g(x) = x + 3x \) is even, odd, or neither, we first simplify the function:
\[ g(x) = x + 3x = 4x \]
Now we will evaluate \( g(-x) \):
\[ g(-x) = 4(-x) = -4x \]
Next, we compare \( g(-x) \) with \( g(x) \) and \(-g(x)\):
-
Check if \( g(x) \) is even:
- A function is considered even if \( g(-x) = g(x) \).
- Here, \( g(-x) = -4x \) and \( g(x) = 4x \).
- Since \( g(-x) \neq g(x) \), the function is not even.
-
Check if \( g(x) \) is odd:
- A function is considered odd if \( g(-x) = -g(x) \).
- Calculate \(-g(x)\):
- \( -g(x) = -4x \).
- We find that \( g(-x) = -4x\) which is equal to \(-g(x)\).
- Since \( g(-x) = -g(x) \), the function is odd.
Since the function is odd, it is also symmetric with respect to the origin.
Final answers:
- The function is odd.
- The function's graph is symmetric with respect to the origin.